Witches and wizards of Hogwarts handbook - Swank, Samantha (New York : Scholastic Inc., 2018)
Looks at the characters from the Harry Potter movies, and includes facts, quotes, and epic moments from the films.
5.0
3-6
Keywords: Harry Potter films -- Miscellanea -- Juvenile literature; Rowling, J. K. -- Characters -- Juvenile literature; Harry Potter films -- Miscellanea; Rowling, J. K. -- Characters